Physiology-Based Pharmacokinetic Study on 18β-Glycyrrhetic Acid Mono-Glucuronide (GAMG) Prior to Glycyrrhizin in Rats - Cao, Mengxin; Zuo, Jiawei; Yang, Jian-Guo; Wu, Chenyao; Yang, Yongan; Tang, Wenjian; Zhu, Lili (Molecules (Basel, Switzerland), 2022)
To understand that 18β-Glycyrrhetic acid 3-O-mono-β-D-glucuronide (GAMG) showed better pharmacological activity and drug-like properties than 18β-Glycyrrhizin (GL); a rapid and sensitive HPLC-MS/MS method was established for the simultaneous determination of GAMG and its metabolite 18β-Glycyrrhetinic acid (GA) in rat plasma and tissues after oral administration of GAMG or GL. This analytical method was validated by linearity, LLOQ, specificity, recovery rate, matrix effect, etc. After oral administration, GAMG exhibited excellent Cmax (2377.57 ng/mL), Tmax (5 min) and AUC0-T (6625.54 mg/L*h), which was much higher than the Cmax (346.03 ng/mL), Tmax (2.00 h) and AUC0-T (459.32 mg/L*h) of GL. Moreover, GAMG had wider and higher tissue distribution in the kidney, spleen, live, lung, brain, etc. These results indicated that oral GAMG can be rapidly and efficiently absorbed and be widely distributed in tissues to exert stronger and multiple pharmacological activities. This provided a physiological basis for guiding the pharmacodynamic study and clinical applications of GAMG.